云南3个主栽品种核桃多肽的制备 及体外抗氧化活性的研究Preparation and in vitro antioxidant activity of polypeptides from three main walnut cultivars in Yunnan - 谢晋祥1，耿树香2，宁德鲁2，庄永亮1，王玺2XIE Jinxiang1, GENG Shuxiang2, NING Delu2, ZHUANG Yongliang1, WANG Xi2 (Zhongguo youzhi, 2025)
为提高云南核桃饼粕附加值，选取云南3个主栽品种深纹核桃（漾泡、三台和细香），采用碱性蛋白酶、木瓜蛋白酶、菠萝蛋白酶对3个品种的脱脂核桃粕粉进行水解制备核桃多肽，对核桃多肽进行模拟胃肠消化，研究核桃多肽及其体外消化产物的抗氧化活性，并对核桃多肽的基本成分、分子质量分布和氨基酸组成进行分析。结果表明：碱性蛋白酶水解制备的核桃多肽的抗氧化能力显著高于木瓜蛋白酶、菠萝蛋白酶水解制备的，而碱性蛋白酶水解制备的3个不同品种核桃多肽的抗氧化活性无显著差异，其中漾泡、三台和细香核桃多肽的DPPH自由基清除率分别为71.34%、71.26%和7182%，ABTS+自由基清除率分别为82.41%、81.23%和82.86%；在经过模拟胃肠消化后，碱性蛋白酶水解制备的核桃多肽的DPPH自由基清除率和ABTS+自由基清除率均有所上升，且其中分子质量小于1 000 Da的小分子多肽组分含量增高；碱性蛋白酶水解制备的漾泡、三台和细香核桃多肽的蛋白质含量均高于50%，必需氨基酸含量分别为122.58、122.84 mg/g和139.19 mg/g，且与抗氧化活性相关的疏水性氨基酸含量较高。综上，云南3种深纹核桃漾泡、三台和细香均适用于碱性蛋白酶水解核桃蛋白进行抗氧化相关功能食品的研发。In order to improve the added value of walnut cake and meal in Yunnan, three main Juglans sigillata D. cultivars (Yangpao walnut, Santai walnut and Xixiang walnut ) in Yunnan were selected, and alkaline protease, papain and bromelain were used to hydrolyze the defatted walnut meal powder of the three cultivars to prepare walnut polypeptides.Simulated gastrointestinal digestion of the walnut polypeptides was carried out, and the antioxidant activity of the walnut polypeptides and their in vitro digestion products were studied. The basic components, molecular weight distribution and amino acid composition of the walnut polypeptides were analyzed.The results showed that the antioxidant activity of walnut polypeptides prepared by alkaline protease hydrolysis was significantly higher than that prepared by papain and bromelain, while there was no significant difference in the antioxidant activity of three cultivars of walnut polypeptides prepared by alkaline protease hydrolysis. The DPPH free radical scavenging rates of Yangpao walnut, Santai walnut and Xixiang walnut polypeptides prepared by alkaline protease hydrolysis were 71.34%, 71.26% and 71.82%, respectively and the ABTS+ radical scavenging rates were 82.41%, 81.23% and 82.86%, respectively.After simulated gastrointestinal digestion, the DPPH free radical scavenging rates and ABTS+ free radical scavenging rates of three cultivars of walnut polypeptides prepared by alkaline protease hydrolysis increased, and the content of small molecular polypeptides components with molecular weight less than 1 000 Da increased.The protein contents of Yangpao walnut, Santai walnut and Xixiang walnut polypeptides prepared by alkaline protease hydrolysis were higher than 50%, the essential amino acid contents were 122.58, 122.84 mg/g and 139.19 mg/g, respectively, the content of hydrophobic amino acids related to antioxidant activity were higher. In summary, the three cultivars of Juglans sigillata D. Yangpao, Santai and Xixiang in Yunnan are suitable for the research and development of antioxidant-related functional foods by alkaline protease hydrolysis of walnut protein.